Inhibition of tryptophan 2, 3-dioxygenase impairs DNA damage tolerance and repair in glioma cells. Issue 2 (9th April 2021) - Reed, Megan R; Maddukuri, Leena; Ketkar, Amit; Byrum, Stephanie D; Zafar, Maroof K; Bostian, April C L; Tackett, Alan J; Eoff, Robert L
Abstract: Expression of tryptophan 2, 3-dioxygenase (TDO) is a determinant of malignancy in gliomas through kynurenine (KYN) signaling. We report that inhibition of TDO activity attenuated recovery from replication stress and increased the genotoxic effects of bis-chloroethylnitrosourea (BCNU). Activation of the Chk1 arm of the replication stress response (RSR) was reduced when TDO activity was blocked prior to BCNU treatment, whereas phosphorylation of serine 33 (pS33) on replication protein A (RPA) was enhanced—indicative of increased fork collapse. Analysis of quantitative proteomic results revealed that TDO inhibition reduced nuclear 53BP1 and sirtuin levels. We confirmed that cells lacking TDO activity exhibited elevated gamma-H2AX signal and defective recruitment of 53BP1 to chromatin following BCNU treatment, which corresponded with delayed repair of DNA breaks. Addition of exogenous KYN increased the rate of break repair. TDO inhibition diminished SIRT7 deacetylase recruitment to chromatin, which increased histone H3K18 acetylation—a key mark involved in preventing 53BP1 recruitment to sites of DNA damage. TDO inhibition also sensitized cells to ionizing radiation (IR)-induced damage, but this effect did not involve altered 53BP1 recruitment. These experiments support a model where TDO-mediated KYN signaling helps fuel a robust response to replication stress and DNA damage. Graphical Abstract: